The physiological role of estrogen receptor functional domains. Issue 6 (26th November 2021) - Arao, Yukitomo; Korach, Kenneth S.
Abstract: Estrogen receptor (ER) is a member of the nuclear receptor superfamily whose members share conserved domain structures, including a DNA-binding domain (DBD) and ligand-binding domain (LBD). Estrogenic chemicals work as ligands for activation or repression of ER-mediated transcriptional activity derived from two transactivation domains: AF-1 and AF-2. AF-2 is localized in the LBD, and helix 12 of the LBD is essential for controlling AF-2 functionality. The positioning of helix 12 defines the ER alpha (ERα) ligand properties as agonists or antagonists. In contrast, it is still less well defined as to the ligand-dependent regulation of N-terminal AF-1 activity. It has been thought that the action of selective estrogen receptor modulators (SERMs) is mediated by the regulation of a tissue specific AF-1 activity rather than AF-2 activity. However, it is still unclear how SERMs regulate AF-1 activity in a tissue-selective manner. This review presents some recent observations toward information of ERα mediated SERM actions related to the ERα domain functionality, focusing on the following topics. (1) The F-domain, which is connected to helix 12, controls 4-hydroxytamoxifen (4OHT) mediated AF-1 activation associated with the receptor dimerization activity. (2) The zinc-finger property of the DBD for genomic sequence recognition. (3) The novel estrogen responsive genomic DNA element, which contains multiple long-spaced direct-repeats without a palindromic ERE sequence, is differentially recognized by 4OHT and E2 ligand bound ERα transactivation complexes.